EFFORTS TO INCREASE CHILDREN'S INTEREST IN LEARNING THROUGH IMAGE MEDIA AT NAPAI SDN WEST WOYLA DISTRICT, WEST ACEH - Mahrini, Mahrini; Sari, Siti Mayang; Mardhatillah, Mardhatillah (Sensei International Journal of Education and Linguistic, 2024)
Education has an important role in the personal formation and intellectual development of children. High interest in learning tends to make students more active, enthusiastic and eager to face the lesson material. On the other hand, low interest in learning can result in boredom, lack of motivation, and even rejection of the teaching and learning process. This research aims to describe efforts to increase children's interest in learning at SDN Napai, West Woyla District, West Aceh Regency, through the use of image media, geographical and social conditions in rural areas are challenges in improving the quality of learning. This research uses a qualitative approach with descriptive research type. Based on the research results, it revealed limited facilities and a lack of variety in learning methods. It is hoped that the implementation of image media at SDN Napai can be an effective solution to stimulate interest in learning. Student reactions to image media were positive, with increased participation and learning outcomes. The role of teachers and parent involvement is very important. Other factors that need to be considered involve the community, developing culturally appropriate materials, and strengthening cooperation. In conclusion, this strategy can have a significant positive impact in increasing children's interest in learning at SDN Napai, in line with the concept of inclusive education and the demands of the digital era.